Spatial distribution of small phytoplankton composition in the Chukchi Sea - Lee, SH; Dahms, HU; Kim, Y; Choy, EJ; Kang, SH; Kang, CK (Polar Biology, 2014)
This study was conducted as part of the second Russian American long-term census of the Arctic in 2009 with sampling across the territorial of the Russian Federation in the Chukchi Sea since recent information regarding the standing stocks of pico- and nano-plankton is very limited. Using flow cytometry, small size fractions of the phytoplankton (< 20 mu m) obtained during the cruise were analyzed for the contributions of pico- and nano-eukaryotic phytoplankton and prokaryotic phytoplankton for the first time in the Chukchi Sea. The salinity and temperature in the southern part were significantly higher than those in the northern part of the Chukchi Sea. The abundance of Prochlorococcus and Synechococcus represented about 30 % of total small phytoplankton cells with their cell abundances reaching 295 and 590 cells ml(-1), respectively, although a significant portion (about 70 %) of the small phytoplankton community (< 20 mu m) was pico- and nano-eukaryotic plankton in the Chukchi Sea. Among different environmental factors, we found that temperature and NH4 concentrations were significantly positively correlated with the abundance of total phytoplankton, pico- and nano-eukaryotes, Prochlorococcus, and Synechococcus. Projected higher water temperature and increase in NH4 concentration condition in the Arctic Ocean as well as the Chukchi Sea could have fostered more small phytoplankton communities especially Prochlorococcus and Synechococcus. X 1 1 4 4 scie scopus